Recent Science from Australian Large-Scale Millimetre Mapping Projects: Proceedings from a Swinburne University Workshop - Bains, I.; Breen, S.; Burton, M.; Cunningham, M.; Jones, P.; Kawamura, A.; Lo, N.; Rowell, G.; Walsh, Andrew (CSIRO, 2009)
Since the recent upgrades to the Australia Telescope National Facility (ATNF) Mopra telescope back-end and receiver system, it has risen from an undersubscribed facility to a sought-after instrument with heavy international competition to gain time. Furthermore, the introduction of the on-the-flymapping capability in 2004 has made this technique one of Mopra's most popular observing modes. In addition, the recent upgrade of the NANTEN millimetre-wavelength telescope to the sub-millimetre NANTEN2 instrument, has provided a complementary, higher-frequency facility to Mopra. A two-dayworkshop was held at Swinburne University in June 2008 to disseminate the current state of ongoing large-scale mapping projects and associated spin-offs that the telescopes' upgrades have facilitated, and to decide upon future research directions. Here, we provide a summary of the result-oriented talks as a record of the state of Australian-access single-dish millimetre science in 2008.